Complex multidisciplinary resection of a malignant rhabdoid tumor of the neck & mediastinum in a pediatric patient - Richard S. Whitlock; Steven C. Mehl; Daniel C. Chelius; John C. Koshy; Joseph L. Mills; Julina Ongkasuwan; Susan L. McGovern; M. Fatih Okcu; Bindi Naik-Mathuria (Elsevier, 2021)
Extrarenal malignant rhabdoid tumors (MRT) are highly aggressive tumors of childhood with a poor overall prognosis. While most commonly found within the kidney and central nervous system, MRT can also occur in other locations and present highly specific challenges for pediatric surgical providers in an effort to achieve a meaningful resection. Cervical rhabdoid tumors are extremely rare. We report the multidisciplinary management of a patient with a complex cervicothoracic malignant rhabdoid tumor who underwent successful surgical resection with a greater than one year survival.